Midiologia, linguagem e poesia - Luciano Barbosa Justino; Simone Dália de Gusmão Aranha (Estudos de Literatura Brasileira Contemporânea)
New possibilities opened up by web communication as regarding its production, circulation and consume, as well as the challenging possibilities that digital cul- ture opens up to literature in its different forms, insofar as they imply signifi- cant changes in their usages, require new theoretical-methodological approaches. However we believe this necessity – although altogether critical – must be con- nected with a reflexion over the technical processes that have directly influenced literature throughout the centuries it has existed. We also think that poetry, main- ly because it has dialogued on a non-stop basis with such processes, has much to tell us about what we hold, following the track of Régis Debray (1995) and Lévy (1997), to be the three ages of intelligence, centered on voice, writing and on digi- tal video.